EFEKTIVITAS PROGRAM UPPKS SEBAGAI USAHA MENINGKATKAN KESEJAHTERAAN KELUARGA MELALUI USAHA EKONOMI: STUDI KASUS KELURAHAN SRIMARTANI, PIYUNGAN, BANTUL - Susianti Susianti (Politeknik Negeri Batam, 2017)
This study aims to determine and analyze the effectiveness and benefit of UPPKS program based on welfare after receiving UPPKS program assistance.Given the importance of improving welfare through family empowerment as a breakthrough to accelerate the transformation of non-socio-economic activities into economic enterprises, it is hoped that through this research, families especially PreSejahtera and KS 1 are able to take advantage of existing business opportunities in the framework of learning productive economic enterprises at the household scale as a business improving family welfare, especially in Srimartani, Piyungan, Bantul. This research is quantitative with judgment sampling method through questionnaires and interviews on UPPKS Program beneficiaries.The effectiveness analysis of the UPPKS Program is done by comparing the realization of the average number of effectiveness of all indicator variables in both input, process and output.While the McNemar test is used to calculate the benefit of the program to the community that follows the UPPKS Program by looking at the significance of the changes.From the research result, it is found that the implementation of UPPKS Program in Srimartani, Piyungan, Bantul based on input, process and output indicator is very effective that is 83.33 percent.And the change in the welfare of respondents is significantly assessed from the aspect of income and working hours before and after following UPPKS Program.